Metrological aspects of researching the specific contact resistivity of ohmic contacts by using the four-contact method - Sheremet, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
In this paper, we have considered the four-contact method for measurements
of the specific contact resistivity of the ohmic contacts (ρc). The presented method for
measuring ρc has been compared with several other methods. Limits of applying this
method have been shown.